An optimised set of criteria of liveable urban ground floor zone - Szerdahelyi-Németh, Klára (4D Journal of Landscape Architecture and Garden Art, 2022)
In our present day it has become a task of great importance to guarantee the liveability of cities constantly increasing in size and density. Special attention must be paid to ensuring that the urban population should feel at home in cities even in the midst of climate change and the continual change in social and economic conditions. Areas, shopping streets and high streets of mixed use and mixed functions in city centres have to face new challenges in our era: the constant change of consumer habits, the emergence of online commerce and, more recently, the patterns of space use changed due to the coronavirus pandemic affect the quality of the urban ground floor zone as a habitat. This study is aimed at summarising and organising the latest present-day research studies revealing the characteristics of the liveable urban ground floor zone. It then summarises the spatial theory, space use and space management characteristics of the liveable urban ground floorzone on the scale of the urban neighbourhood, the street and the building based on the review of literature. Based on a questionnaire and qualitative interviews conducted with domestic experts, it then adapts the revealed characteristics to the Hungarian social, cultural, architectural and climatic features. It thus integrates the characteristics of the liveable urban ground floor zone, the latest results of contemporary urban research and the knowledge of Hungarian experts on the subject into a single framework. A further aim of the research is to help our understanding of the changes in the urban ground floorzone regarding spatial theory, land use and space management, as well as support the identification of the planned interventions in addition to offering responses to spontaneous processes of urban development. The set of criteria established during the phases of reviewing the literature, summarising, evaluation and the participatory process helps the launch of further research, and it can be used as a research method while it can provide a complex and fresh basis for the elaboration of urban development programs and the participation of local communities in planning. The results of the research can be applied primarily in the city centre areas of terraced housing, during the development of the groundfloor zones along main roads and high streets.
Keywords: liveable city; liveable city centre area; urban ground floor zone; main street